A sensitive spectrophotometric assay for peroxisomal acyl-CoA oxidase. - Small, G M (1985)
A simple spectrophotometric assay was developed for peroxisomal fatty acyl-CoA oxidase activity. The assay, based on the H2O2-dependent oxidation of leuco-dichlorofluorescein catalysed by exogenous peroxidase, is more sensitive than methods previously described. By using mouse liver samples, cofactor requirements were assessed and a linear relationship was demonstrated between dye oxidation and enzyme concentration. By using this assay on subcellular fractions, palmitoyl-CoA oxidase activity was localized for the first time in microperoxisomes of rat intestine. The assay was also adapted to measure D-amino acid oxidase activity, demonstrating the versatility of this method for measuring activity of other H2O2-producing oxidases.